(3LGeY GdCOhjIs - (3MGeO Hf SeLhf, CHh HcQ,J (B400 (3g` s
(3ChdgG (B:s
(3MQa Gdfhf fGQMjd bGd CHh MfjaI GdOjfhQi GdhGMOI fGQMjdI hgh LhR GdgfO hjbGd dg CjVkG HGQfL s
(3BNQgG (B:s
(3GdQGRi ai GdefUhQi GdVQ hfGaY ef GSJWdGb GdHWf hGdbdGY ZGjIGdfaY ced GdLRA GdJGSY ef GdCOhjI GdeaQOI dGHf SeLhf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B161s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B51s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs